Diplomatic tales: diplomacy as myth construction in Brazil - Estre, Felipe Bernardo (2022)
This work seeks to understand the relationship between diplomacy and academia in the constitution of the discipline of International Relations in Brazil. Based on discourse analysis and intertextuality, this thesis investigates the founding myth of IR in Brazil and how it impacts the production of knowledge in the area. This myth places diplomats in a privileged position as knowledge producers in IR. Consequently, organizational myths about the Brazilian Foreign Ministry, commonly referred to as Itamaraty, are assimilated by academics, creating analytical blind spots. Thus, more than a way of operating in the international system, Brazilian diplomacy becomes a creator of myths that expand Itamaratys influence capacity.